A Comparison of Digital Modelling Techniques Analyzing a Section of Qhapaq Nan - Retamozo, S (2015)
Total Station has been one of the most common acquisition devices for achieving maps through topographic survey. Nowadays, Terrestrial Laser Scanner (TLS) and Photogrammetry are commonly used to generate accurate meshes. In addition, commercial products such as Kinect offer low cost technology to acquire point-cloud information. The present paper aims to measure the accuracy of these digital modelling techniques by employing elevation contour maps, surface deviations and distance measurements. For this purpose, a 450 m sector of the Qhapaq Nan located in Lima-Peru, was selected as a case of study. A camera-enabled drone was used for acquiring pictures to obtain a high-resolution photogrammetric model. Subsequently, a 3D survey of the monument was conducted with a time-of-flight laser scanner. Contour elevation lines where extracted from TLS, Photogrammetry and Total Station models at the same depths in order to determine the precision of photogrammetry and laser scanner reconstructions. In addition, geometrical comparisons were performed among the 3D models above mentioned and the Kinect sensor. The comparison showed that TLS is the most accurate tool for 3D reconstruction. However, Photogrammetry and Kinect provided errors of less than one centimeter in accuracy.